Alcohol Abuse, Endoplasmic Reticulum Stress and Pancreatitis - Pandol, Stephen J. (S. Karger AG, 2011)
Alcohol abuse is a common cause of both acute and chronic pancreatitis. There is a wide spectrum of pancreatic manifestations in heavy drinkers from no apparent disease in most individuals to acute inflammatory and necrotizing pancreatitis in a minority of individuals with some progressing to chronic pancreatitis characterized by replacement of the gland by fibrosis and chronic inflammation. Both smoking and African-American ethnicity are associated with increased risk of alcoholic pancreatitis. In this review we describe how our recent studies demonstrate that ethanol feeding in rodents causes oxidative stress in the endoplasmic reticulum (ER) of the digestive enzyme synthesizing acinar cell of the exocrine pancreas. This ER stress is attenuated by a robust unfolded protein response (UPR) involving X-box binding protein-1 (XBP1) in the acinar cell. When the UPR activation is prevented by genetic reduction in XBP1, ethanol feeding causes significant pathological responses in the pancreas. These results suggest that the reason most individuals who drink alcohol heavily do not get significant pancreatic disease is because the pancreas mounts an adaptive UPR to attenuate the ER stress that ethanol causes. We hypothesize that disease in the pancreas results when the UPR is insufficiently robust to alleviate the ER stress caused by alcohol abuse.